Multi‐objective linear fractional inventory model with possibility and necessity constraints under generalised intuitionistic fuzzy set environment. Issue 3 (20th August 2019) - Garai, Totan; Garg, Harish
Abstract : This study presented a multi‐objective linear fractional inventory (LFI) problem with generalised intuitionistic fuzzy numbers. In modelling, the authors have assumed the ambiances where generalised trapezoidal intuitionistic fuzzy numbers (GTIFNs) used to handle the uncertain information in the data. Then, the given multi‐objective generalised intuitionistic fuzzy LFI model was transformed into its equivalent deterministic linear fractional programming problem by employing the possibility and necessity measures. Finally, the applicability of the model is demonstrated with a numerical example and the sensitivity analysis under several parameters is investigated to explore the study.